1991
DOI: 10.1111/j.1471-0528.1991.tb15340.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of induced abortion on subsequent pregnancy outcome

Abstract: Objective-To investigate the effect of induced abortion on the outcome of the next pregnancy. Design-Long-term prospective controlled cohort study. Setting-Joint Royal College of General Practitioners/Royal College of Obstetricians and Gynaecologists study based in gencral practice in England, Scotland and Walcs. Subjects-1311 women whose recruitment pregnancy had ended in induced abortion (the abortion group) and 2131 women whose recruitment pregnancy had a natural conclusion (the non-abortion group). Muitz o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 17 publications
1
17
0
2
Order By: Relevance
“…Other studies that investigated this association did not find an increased risk. 33,34 Most studies that have investigated risk factors for stillbirth have not included data on history of previous induced abortion(s). [35][36][37] Further prospective studies are necessary to explore this association.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies that investigated this association did not find an increased risk. 33,34 Most studies that have investigated risk factors for stillbirth have not included data on history of previous induced abortion(s). [35][36][37] Further prospective studies are necessary to explore this association.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Spreading of public awareness in media, conferences, seminars, ladies clubs and patients visiting us about selfconsumption of these drugs leading to their abuse and health hazards is the need to the day. 5 The sale of these drugs at pharmacies without prescription should be regulated and checked. [6][7][8][9] Many a times important aborted tissue for histopathology in hydatiform mole is lost due to bleeding at home and patients presenting later at Gynaic OPD, pregnancies, continuing to persist even after pills leading to 2 nd trimester abortions with its added health hazard is also very common.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have concluded that SA in the first trimester does not increase the risk of adverse outcome in subsequent pregnancies [3,4], but many women desiring to terminate a pregnancy prefer the MA approach because it is convenient, inexpensive, and noninvasive [5]. Medical abortion is easily performed without invading a woman's privacy and may actually cause fewer injuries to the uterus and cervix than SA [6], and its shortterm adverse effects are generally minor [7].…”
Section: Introductionmentioning
confidence: 96%